2014
DOI: 10.5433/2316-5200.2014v3n1p33
|View full text |Cite
|
Sign up to set email alerts
|

Composição química e propriedades tecnológicas de duas cultivares de soja

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 5 publications
1
1
0
4
Order By: Relevance
“…Other studies that analyzed soybean grain samples from the state of Paraná also found similar variations for the physical-chemical parameters analyzed in this study, where the total lipid content showed variations of 18.16-23.86%, crude protein varied from 32.91 to 39.41%, and the moisture ranged from 6.70 to 8.50% (Ferreira et al, 2014;Gonçalves et al, 2014).…”
Section: Resultssupporting
confidence: 81%
“…Other studies that analyzed soybean grain samples from the state of Paraná also found similar variations for the physical-chemical parameters analyzed in this study, where the total lipid content showed variations of 18.16-23.86%, crude protein varied from 32.91 to 39.41%, and the moisture ranged from 6.70 to 8.50% (Ferreira et al, 2014;Gonçalves et al, 2014).…”
Section: Resultssupporting
confidence: 81%
“…The highest Zn content was approximately 45% when 2.73 mg L -1 Zn was applied. Previous studies carried out with soybean grains recommended for human consumption reported that the grains contained 16 to 22% lipids and 23 to 43% protein (Gonçalves et al, 2014;Ciabotti et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Diferentemente de Gonçalves et al 20 No período inicial, o índice de acidez do óleo extraído dos grãos de soja nos dois teores de água não diferiu. No segundo mês de armazenamento houve diferença nos grãos armazenados a 35 °C, obtendo uma maior acidificação do óleo de grãos com teor de água de 13,84% (bu).…”
Section: Resultsunclassified
“…Gonçalves et al 20 observaram valores de proteína bruta para grãos de soja das cultivares BRS 284 e BMX Potência RR de 33,24 e 34,74%, respectivamente. Delarmelino-Ferraresi et al 25 em seus estudos concluíram que a composição química varia entre lotes e cultivares, sendo que o aumento de proteína corresponde a redução do óleo e que os teores de proteína, óleo e ácidos graxos livres evidenciam a relação entre a composição química e a qualidade fisiológica das sementes de soja.…”
Section: Resultsunclassified
See 1 more Smart Citation